Mixture formation of OME3−5 and 1-Octanol in comparison with diesel-like Dodecane under ECN Spray A conditions - Strauß, Lukas; Rieß, Sebastian; Wensing, Michael (Frontiers in Mechanical Engineering, 2023)
In order to be able to use the full potential of regenerative fuels, a comprehensive characterization is necessary to identify the differences between conventional fuels and regenerative fuels. In the current work, we compare OME3−5 and 1-Octanol with diesel-like Dodecane in terms of mixture formation under ECN Spray A conditions for single and multi-injection. To determine the mixtures, i.e., the mass distribution and the resulting air-fuel equivalence ratio, Naber and Siebers’ model as well as Musculus and Kattke’s model are used, which are based on experimental data. For this work, the mass flow rates and also the liquid and gaseous penetration depths of the fuel spray are measured. Results show that the mass ratios for the quasi-steady state of a single main injection for all three fuels are nearly the same, whereas the air-fuel equivalence ratios are very different. In addition, multiple injections are used to show that the fuel influences the opening and closing behavior of the injector. In the transient case of multiple injections, completely different mixtures result. In summary, it can be stated that OME3−5 and also 1-Octanol show a clearly different physio-chemical behavior from Dodecane and cannot simply be used as a drop-in fuel. Therefore, a simple exchange is not possible without major adaptations.